Use the substitution tan x = p.

Differentiating, the result will be: `dx/(cos^2 x) = dp`

Integrate:

`int e^(tan x)dx/(cos^2 x) = int e^p dp = e^p + c`

Substitute back p = tan x

`int e^(tan x)dx/cos^2 x = e^(tan x) + c`

**ANSWER: The result of integration is **

`int e^(tan x)dx/(cos^2 x) = e^(tan x) + c`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now